Visualized texts : sacred spaces, spatial texts and the religious cartography of Banaras - Gengnagel, Jörg (Ethno-Indology, 2011)
The study of the history of South Asian cartography has long been interpreted based on Western cartographic traditions. Maps of the South Asian subcontinent were assumed to be produced by foreigners - not by South Asians themselves. Maps actually produced in South Asia were neglected as a category in their own right. The present study focuses on the religious cartography of Banaras. It deals with visualizations of the sacred topography of Banaras as represented by various kinds of "maps", including painted pictorial maps, printed pilgrimage maps and simple spatial charts. The introduction to t.